Search for a narrow t(t)over-bar resonance in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Wayne, M.; et al. (Amer Physical Soc, 2012)
We report a search for a narrow t (t) over bar resonance that decays into a lepton + jets final state based on an integrated luminosity of 5.3 fb(-1) of proton-antiproton collisions at root s = 1.96 TeV collected by the D0 Collaboration at the Fermilab Tevatron Collider. We set upper limits on the production cross section of such a resonance multiplied by its branching fraction to t (t) over bar. We exclude a leptophobic topcolor Z' at the 95% confidence level for masses below 835 GeV (940 GeV) if its width is 1.2% (3%) of its mass. We also exclude color octet vector bosons (colorons) with masses below 775 GeV.